Physiological frailty in chronically homeless young adults determined by handgrip strength - Ali Ruiz Coronel; Rubén Fossión; Josué Sauri García (Social Medicine Publication Group, 2019)
If there are only few studies on homelessness, scientific research addressing the physiological conditions of the homeless are almost nil. In order to examine the feasibility of such investigations, we conducted a study analyzing the prevalence of frailty among fifty chronically homeless young adults in Mexico City through measuring their handgrip strength and then comparing it with the same information gathered from a group of 50 university students who had never been homeless and who comprised a control sample. The frailty syndrome has more often been associated with aging and chronic illnesses. Its presence in homeless young adults proves that it can also be caused by adverse life conditions. This supports the idea that their general health is an index of the social suffering, stress, exclusion and violence that they have to deal with on a daily basis and that it causes an accelerated aging that explains their high mortality index. This study is part of a wider ethnographical research effort that seeks to better understand their general state of being and improve it through more precisely designed interventions that are relevant to their skills and capacities.